Ilmu dan Islam: Mengurai Konsep dan Sumber Ilmu dalam Al-Qur - Rahman, Fadli; Barni, Mahyuddin (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2021)
This study aims to explore the meaning or concept of the word